Nutritional evaluation and surgical morbimortality of neoplasic patients. - Bertullo, Hugo; Muguruza, Alvaro; Duarte, Gladys; Ferradas, Ana (Cirugía del Uruguay, 1985)
Study of forty surgically neoplasic patients that were evaluated and nutritionally recovered through a single protocol. Discussed are !he value of !he notion of posing weight and its statiscally significan! relation with plasmatic proteins and immunily bu! no with !he extent of !he neoplasm. In very poor surgical risk patients, emphasis is laid on precise nutritional indication as far as !he surgical procedure is concerned and complications inherent in such practice, concluding lhey are acceptabl:; considering benefits, and !he complications inherent in same.